Effect of Administration of Copper plasma Activated water and Anesthetic on Hematological and Pancreatic tissues of Wister rats - Umaru, Isaac John; Kingsly, Iseko Iyoko; Gyasi, Prince Kwadwo; Ogochukwu, Edom Favour; Akafa, Tensaba Andes; Malantso, Jackson Soyinka; Habibu, Bilyaminu; Umaru, Kerenhappuch Isaac (African Journal of Biochemistry and Molecular Biology Research, 2025)
In biomedicine, applications of PAW span from biofilm removal, wound healing, deactivation of bacteria and viruses, dentistry (for teeth disinfection and whitening), and cancer therapy. The biochemical activity of PAW is derived from synergistic effects of the highly reactive species, specifically reactive oxygen and nitrogen species (RONS). PAW is considered a biofriendly and prospective solution for biotechnology applications due to the time dependent nature of its biochemical activity because of the active species, and its economic and environmental benefits of using air rather than toxic chemicals as the raw material. Thus, the study on Effect of Administration of Copper plasma Activated water and Anaesthetic on Haematological and Pancreatic tissues of Wister rats. Material and Methods: Preparation of plasma-activated water a non-thermal micro-hollow cathode discharge (MHCD) was used to generate plasma-activated waters (CU-PAWs). Results: The results showed the haematological profile of the animals treated with 400mgkg-' had a decrease in Haemoglobin, Mean capsular Haemoglobin (11.21 ± 1.23 and 22.93 ± 21.11) compared to the controlled group (15.03 ± 1.72 and 29.93 ± 7.27) and in animals treated with 200mgkg-1 and 400mgkg-1 there is a significant decrease in the platelets (21.96 ± 23.16 and 20.89 ± 24.03) compared to animals on control group (32.08± 16.70) (table 2). Animals treated with 200mgkg-' and 400mgkg-' have a decrease in platelet (22.36 ± 4.88 and 20.89 ± 24.03) compared to animals on control (32.08 ± 16.70) and also animals treated with 400mgkg-1 have an elevated white blood cell count 173-56 ± 4.50) compared to the control group (3.66 ± 3.06). Conclusion: Cupper plasma water is safe to be used since it do not have much effect on the blood biochemistry and haematological parameters unlike the aesthetic agents cause changes on the haematological and blood biochemistry parameters. Hence, it is important to be aware of the effects of these agents before using them in experiments.